Plasmaphresis therapy for pulmonary hemorrhage in a pediatric patient with IgA nephropathy - Dae-Kyoon Yim; Sang-Taek Lee; Heeyeon Cho (Korean Pediatric Society, 2015)
IgA nephropathy usually presents as asymptomatic microscopic hematuria or proteinuria or episodic gross hematuria after upper respiratory infection. It is an uncommon cause of end-stage renal failure in childhood. Pulmonary hemorrhage associated with IgA nephropathy is an unusual life-threatening manifestation in pediatric patients and is usually treated with aggressive immunosuppression. Pulmonary hemorrhage and renal failure usually occur concurrently, and the pulmonary manifestation is believed to be caused by the same immune process. We present the case of a 14-year-old patient with IgA nephropathy who had already progressed to end-stage renal failure in spite of immunosuppression and presented with pulmonary hemorrhage during oral prednisone treatment. His lung disease was comparable to diffuse alveolar hemorrhage and was successfully treated with plasmapheresis followed by oral prednisone. This case suggests that pulmonary hemorrhage may develop independently of renal manifestation, and that plasmapheresis should be considered as adjunctive therapy to immunosuppressive medication for treating IgA nephropathy with pulmonary hemorrhage.